Named Entity Recognition (NER) System for Hindi Language Using Combination of Rule Based Approach and List Look Up Approach (International Journal of Scientific Research and Management (IJSRM), 2015)
Named Entity Recognition is a discipline for recognition of named entities in a document associating them with the proper types. Information Extraction is the main requirement of Named Entity Recognition (NER) system. The main functionality of NER is to identify Named Entities. Named Entities can be name of a Person, Location name, Organization name, Time, Date, etc. The NER is a major application of Natural Language Processing (NLP). In proposed system, a NER system is designed and implemented by using Hybrid Approach for Hindi Language. Hybrid Approach is the combination of Rule Based Approach and List look Approach. Named entities have been identifying by using some existing rules and adding new rules. Named entities have been stored in corpus; from here named entities have been identified from corpus. The accuracy of the proposed system comes out to be approximately 96%.